2019
DOI: 10.1159/000499685
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 Mediates Pyroptosis of Tubular Epithelial Cells and Septic Acute Kidney Injury

Abstract: Background/Aims: Acute kidney injury (AKI) is a serious complication of sepsis and has a high morbidity and mortality rate. Caspase-11 induces pyroptosis, a form of programmed cell death that plays a critical role in endotoxic shock, but its role in tubular epithelial cell death and whether it contributes to sepsis-associated AKI remains unknown. Methods: The caspase-11–/– mouse received an intraperitoneal injection of lipopolysaccharide (LPS, 40 mg/kg body weight). Caspase-11–/– renal tubular epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Pyroptosis is a form of inflammatory programed cell death pathway activated by human and mouse caspase1 and release of proinflammatory cytokines, including interleukin- (IL-) 1 β [ 39 ]. Pyroptotic cell death has been confirmed in LPS-induced AKI [ 15 ]. Our results show that mitochondria fission precedes caspase1 and IL-1 β activation involved pyroptosis occur in LPS-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis is a form of inflammatory programed cell death pathway activated by human and mouse caspase1 and release of proinflammatory cytokines, including interleukin- (IL-) 1 β [ 39 ]. Pyroptotic cell death has been confirmed in LPS-induced AKI [ 15 ]. Our results show that mitochondria fission precedes caspase1 and IL-1 β activation involved pyroptosis occur in LPS-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, caspase1 cleaves pro-IL-1 β into their mature forms, to induce pyroptosis [ 14 ]. Pyroptosis is involved in the death of renal tubular epithelial cells after exposure to microbial infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the injection of IOP into mouse also increased the percentage of caspase-1 (+) PI (+) cells, IL-1β and IL-18 levels, LDH release activity, and the relative expression of NLRP3, ASC, caspase-1, GSDMD, and IL-1β. A previous study reported that caspase-11-mediated pyroptosis is closely related with Lipopolysaccharides (LPS)-induced septic AKI [36][37]. It is also reported that kidney epithelial pyroptosis played requisite roles in CI-AKI [38].…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, this is the first study to report PD-induced NLRP3 inflammasome inactivation as a molecular mechanism of mitophagy in SI-AKI. Increasing studies have reported that inflammasome formation-induced activation of pyroptosis plays an important role in inflammatory diseases, including SI-AKI [39][40][41]. In the future, the effects of PD and sirtuins on pyroptosis should be explored further to identify more treatment targets for SI-AKI.…”
Section: Discussionmentioning
confidence: 99%